2019
DOI: 10.3389/fmars.2019.00656
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Photosynthetic Electron Transfers and Bleaching Phenotypes Upon Acute Heat Stress in Symbiodinium and Breviolum spp. (Symbiodiniaceae) in Culture

Abstract: The breakdown of the symbiosis between cnidarians and Symbiodiniaceae often occurs upon periods of elevated sea surface temperature and gives rise to bleaching events that affect coral reefs worldwide. In this respect, an impairment of photosynthesis would be responsible for light-dependent generation of toxic reactive oxygen species putatively contributing to death of symbionts and/or host cells. In some Symbiodiniaceae species, alternative photosynthetic electron flows (AEF) have been documented to occur upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 65 publications
6
23
2
Order By: Relevance
“…In the present study, rETR PSII and E O both saturated at light intensities above 300 µmol photons m −2 •s −1 and 600 µmol photons m −2 •s −1 at the beginning of the experiment and after 3 weeks of bicarbonate and ammonium supplementation, respectively ( Figure S6). However the shape of the relationship between both parameters (i.e., linear) differed from those previously reported in [53] and more recently in [52] (i.e., non-linear with net VO 2 saturating more rapidly than rETR PSII ). Finally, the calcification rate measured in the iC & iN condition was also higher than in the control condition (P = 0.006; Figure S5) but similar to the rates measured in the other experimental treatments.…”
Section: Effects Of the Combined Supply Of Ammonium And Bicarbonate Ccontrasting
confidence: 90%
See 1 more Smart Citation
“…In the present study, rETR PSII and E O both saturated at light intensities above 300 µmol photons m −2 •s −1 and 600 µmol photons m −2 •s −1 at the beginning of the experiment and after 3 weeks of bicarbonate and ammonium supplementation, respectively ( Figure S6). However the shape of the relationship between both parameters (i.e., linear) differed from those previously reported in [53] and more recently in [52] (i.e., non-linear with net VO 2 saturating more rapidly than rETR PSII ). Finally, the calcification rate measured in the iC & iN condition was also higher than in the control condition (P = 0.006; Figure S5) but similar to the rates measured in the other experimental treatments.…”
Section: Effects Of the Combined Supply Of Ammonium And Bicarbonate Ccontrasting
confidence: 90%
“…. ) in various species of Symbiodiniaceae isolated in culture [52,53]. In the present study, rETR PSII and E O both saturated at light intensities above 300 µmol photons m −2 •s −1 and 600 µmol photons m −2 •s −1 at the beginning of the experiment and after 3 weeks of bicarbonate and ammonium supplementation, respectively ( Figure S6).…”
Section: Effects Of the Combined Supply Of Ammonium And Bicarbonate Csupporting
confidence: 57%
“…Besides, in several species of Symbiodiniaceae in culture, a high light-dependent oxygen uptake was found to occur at the acceptor side of PSI through a Mehler-type reaction 37,38 . As illustrated in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…in culture activates a light-enhanced dark respiration during photosynthesis 8 . A more detailed characterization through the combination of various techniques (O 2 exchange, PSII chlorophyll a fluorescence emission, PSI primary electron donor [P700] absorbance change in the far-red spectrum, and analysis of the thylakoid transmembrane electric field), revealed that an oxygen-dependent reduction at the acceptor side of PSI occurs as photoprotective mechanism in Symbiodinium isolates 37 , 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, mounting evidence has shown that bleaching was strongly correlated with the disrupted dynamic equilibrium of host–symbiont relationships (Rosenberg et al ., ; Bourne et al ., ; Ricci et al ., ), which favour opportunistic and potentially pathogenic bacteria coupled to the physiological impairment of the holobiont (Cárdenas et al ., ; Roder et al ., ). Thus, the dysbiosis of coral holobiont microbiome has increasingly become an important factor leading to bleaching (Mao‐Jones et al ., ; Dang et al ., ).…”
Section: Introductionmentioning
confidence: 97%